Cardiorespiratory Fitness May Protect Memory for Poorer Sleepers - Kuhn, Tara; Heisz, Jennifer (Frontiers in Psychology, 2022)
Objectives: Physical activity has been shown to protect executive functions against the deleterious effects of poorer sleep among older adults; however, it is unknown whether memory is protected too, and if this relationship differs by age. The present study investigated the relationship between cardiorespiratory fitness, sleep, and memory in both older and young adults. Methods: This observational study recruited twenty-six older adults (70.7 ± 2.8 years) and thirty-five young adults (21.0 ± 3.1 years). Participants completed the Rockport 1-mile walk test to evaluate cardiorespiratory fitness. Participants wore an actigraph for one week to measure habitual sleep and returned for a second visit to perform the memory tests. The interaction between cardiorespiratory fitness and sleep to predict memory was assessed separately in older adults and younger adults. Results: In older adults, cardiorespiratory fitness significantly moderated the relationship between memory and sleep quality, specifically number of nighttime awakenings, sleep efficiency, and wake after sleep onset. Further analyses reveal that a high number of nighttime awakenings and low sleep efficiency significantly predicted worse memory performance in the low fit older adults, but high fit older adults. Notably, every nighttime awakening was associated with a nearly 4% decrease in memory in low fit older adults, but not high fit older adults. Wake after sleep onset did not significantly predict memory in either fitness group. No interaction was found when looking at sleep duration or self-report sleep quality in older adults and no significant interactions were observed between fitness, sleep, and memory in younger adults. Conclusions: Overall, the results suggest that cardiorespiratory fitness may act as a protective buffer for memory in older adults with poor sleep quality. These same was not true for younger adults suggesting that the protective effects of cardiorespiratory fitness on sleep-related memory impairments may be age specific.